2023
DOI: 10.1039/d3ob01487h
|View full text |Cite
|
Sign up to set email alerts
|

Serine-mediated hydrazone ligation displaying insulin-like peptides on M13 phage pIII

Yi Wolf Zhang,
Nan Zheng,
Danny Hung-Chieh Chou

Abstract: Phage display has emerged as a tool for the discovery of therapeutic antibodies and proteins. However, the effective display and engineering of structurally complex proteins, such as insulin, pose significant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We also demonstrated that omniligase-1 could specifically mediate the ligation of substrates to phage pIII protein with high efficiency and conversion rate while not targeting other phage coat proteins. This new approach circumvents the need for specific epitopes on phage, as required by Sortase A, or chemical modifications, , thereby expanding the substrate scope and enhancing the diversity of phage display libraries. Our two-chain insulin phage display system enabled the rapid construction of a highly diverse insulin library within 24 h. Through the screening of this library against IR, we identified several new insulin ligands from randomized sequences that displayed activity comparable to hIns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that omniligase-1 could specifically mediate the ligation of substrates to phage pIII protein with high efficiency and conversion rate while not targeting other phage coat proteins. This new approach circumvents the need for specific epitopes on phage, as required by Sortase A, or chemical modifications, , thereby expanding the substrate scope and enhancing the diversity of phage display libraries. Our two-chain insulin phage display system enabled the rapid construction of a highly diverse insulin library within 24 h. Through the screening of this library against IR, we identified several new insulin ligands from randomized sequences that displayed activity comparable to hIns.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that omniligase-1 could specifically mediate the ligation of substrates to phage pIII protein with high efficiency and conversion rate while not targeting other phage coat proteins. This new approach circumvents the need for specific epitopes on phage, as required by Sortase A, 7 or chemical modifications, 55,56 thereby expanding the substrate scope and enhancing the diversity of phage display libraries.…”
Section: ■ Conclusionmentioning
confidence: 99%